Impacts of the Covid-19 pandemic on criminal justice journeys of adult and child survivors of sexual abuse, rape and sexual assault, 2020-2022: [data collection] - O'Doherty, Lorna (UK Data Service, 2022)
Over 150000 sexual offences were recorded by police in year ending March 2020 (ONS, 2020), and there are indications that the Covid-19 lockdown increased some sexual offences (e.g. online -facilitated abuse, or sexual abuse perpetrated by family members) and decreased others (e.g. assaults by strangers/peers). However, there has been no research into the specific effects of Covid-19 on criminal justice system (CJS) policies and practices relating to sexual offences, nor on the journeys of survivors through the CJS during this period. Prior to the pandemic, there were significant challenges for the investigation and prosecution of sexual offences and conviction rates were extremely low. Some of these challenges may well have been exacerbated by Covid-19 and lockdown e.g. further delays to investigating cases, postponement of Achieving Best Evidence interviews. At the same time, however, Covid-19 has generated significant innovation within the CJS, e.g. the introduction of a video platform within the courts enabling all parties in a criminal hearing to engage securely and remotely, and this may sow the seeds for improvement in survivors’ journeys through the CJS. Drawing on the perspectives and experiences of CJS stakeholders, including complainants and families, police, Crown Prosecution Service, HM Courts and Tribunals Services, the Judiciary, Sexual Assault Referral Centres (SARCs), and Independent Sexual Violence Advisors, this project provide unique insights into the impact of the pandemic on the CJS in sexual offence cases. The data shared here is based on 72 interviews conducted with survivors/family members, and professionals from the police, SARCs and the third sector. The findings identify how the pandemic has exacerbated existing challenges, posed new difficulties, and provoked innovations that could improve the experiences of victims and survivors of sexual violence and abuse. Over 150000 sexual offences were recorded by the police in the year ending March 2020 (ONS, 2020), and there are indications that lockdown increased some sexual offences (e.g. online-facilitated abuse, sexual abuse perpetrated by family members) and decreased others (e.g. assaults by strangers/peers). However, there has been no research into the specific effects of Covid-19 on criminal justice system (CJS) policies and practices relating to sexual offences, nor on the journeys of survivors through the CJS during this period. Prior to the pandemic, there were significant challenges for the investigation and prosecution of sexual offences and conviction rates were extremely low. Some of these challenges may well have been exacerbated by Covid-19 and lockdown e.g. further delays to investigating cases, postponement of Achieving Best Evidence interviews. At the same time, however, Covid-19 has generated significant innovation within the CJS e.g. the introduction of a video platform within the courts enabling all parties in a criminal hearing to engage securely and remotely, and this may sow the seeds for improvement in survivors' journeys through the CJS. Drawing on the perspectives and experiences of CJS stakeholders, including complainants and families, police, Crown Prosecution Service, HM Courts and Tribunals Services, the Judiciary, Sexual Assault Referral Centres, and Independent Sexual Violence Advisors, this research will provide unique insights into the impact of the pandemic on the CJS in sexual offence cases. Changes to procedures precipitated by Covid-19 might offer longer-term benefits for survivors and stakeholders and we aim to identify these and promote their implementation.